Solitary extramedullary plasmacytoma in the lung misdiagnosed as lung cancer: A case report and literature review - Wang, Jingjing; Yang, Xiaoyun; Liu, Xiaomei; He, Tao; Liu, Bin; Yang, Lei; Yuan, Fei; Li, Jing (Frontiers in Oncology, 2022)
Background: Extramedullary plasmacytoma (EMP) is an extremely rare kind of soft tissue plasma cell neoplasm without bone marrow involvement or other systemic characteristics of multiple myeloma. Primary pulmonary plasmacytoma (PPP), with no specific clinical manifestations, is an exceedingly rare type of EMP. Because of its complexity, PPP is often difficult to diagnose. Computed tomography-guided percutaneous core needle biopsy (CT-guided PCNB) has been shown to have high sensitivity, specificity and accuracy for characterization of pulmonary lesion, particularly if malignancy is suspected. Here we presented a rare case of PPP diagnosed with CT-guided PCNB. Case presentation: A 78-year-old female smoker who visited our outpatient clinic for a mass in the left lower lobe of the lung. Pathological based on CT-guided PCNB yielded a PPP with no lymph node or other distant metastasis. Conclusions: Extramedullary plasmacytoma should be considered in the differential diagnosis of a pulmonary mass.